Comparative study on maternal morbidity in elective and emergency caeserean section at tertiary hospital - Meena, Pragati; Meena, Seema; Sharma, Bharti; Chaudhary, Richa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: The incidence of caesarean sections has significantly increased over the previous thirty years and nearly doubled in the current decade, because of more liberalisation of indications of caesarean sections. India’s caesarean section rates have surpassed the WHO cutoff point of 15%, raising serious public health issues. The prevalence of the C-section in India was 8.5% in NFHS-3 while data in NFHS-4 show that it has increased to 17.2%. Thus, almost 9% has increased over 10 years. Objective was to compare the maternal morbidity in elective and emergency caesarean section. Methods: Institution based comparative study was conducted among 108 females undergoing lower segment caesarean section at JNUIMSRC, Jaipur. After taking written informed consent patients were enrolled for the study. Once the data was collected it was analysed as per appropriate statistical analysis. Results: Incidence of emergency LSCS was 23.6% and of elective LSCS was 76.4%. the most common maternal indication was previous LSCS (38.1%) and most common fetal indication was fetal distress (13.3%) followed by malpresentation (11.4%). Incidence of intraoperative complications was 29% with most common complications being atonic PPH (12.4%) followed by traumatic PPH (5.9%), bladder and bowel injury (0.7%). Incidence of post operative complications was 51.9% with most common being anaemia (20.8%), PPH (10%), puerperal sepsis (8%). Conclusions: If performed for medical reasons, CS can save the lives of both mothers and babies. Therefore, CSs should preferably only be performed when necessary for medical reasons. Morbidity is more with emergency LSCS than elective LSCS with PPH being the most common intraoperative complication and anemia being most common post operative complication.